Methodology of analysis of the condition of the pavement starting from the deflection bowl - Andrade Neto, Carlos (2025)
Presently work is exposed a methodology that allows to carry out an intervention proposal with regard to the rehabilitation of the pavement, as well as the determination of the reinforcement thickness, starting from the parameters of the deflection bowl. They are obtained, on the base of the structures regulated in the norm of SATCC, 2001 (Southern Africa Transport and Communications Commission), and the use of the computation program JULEA, the corresponding answer surfaces starting from the indexes of the deflection, what allows to formulate the mathematical expressions to estimate the module and the condition of each one of the layers of the structure of the pavement and the equation for the calculation of the thickness reinforcement. The results of the methodology are shown applied in a study case, where they are carried out confirmations of the deflection with the Benkelman beam and the use of the Falling Weight Deflectometer (FWD), being verified the validity of the proposed procedure that increase the speed in the obtaining of the results of the diagnosis and rehabilitation solutions.